Guidance and Counseling Programs That Can Be Implemented to Improve Student Work Readiness - Setiawati, Setiawati; Azkiyah, Nurul; Budiamin, Amin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Sixth-semester students are 19-22 years old to be declared as early adult individuals. The tasks of early adult development include choosing a spouse/marriage partner and starting to work in a position. The sixth-semester student work readiness is still worried about the lack of knowledge and competence to support their future careers. This study aims to: 1) describe the level of student work readiness; and 2) describe guidance and counseling programs that can be implemented to improve student work readiness. This research was conducted on students of S-1 Guidance and Counseling students class of 2017 FIP UPI. This research is a descriptive quantitative research method with work readiness variables. The research sample consisted of 74 students with a sampling technique using a nonprobability sampling approach with a saturated sampling technique that did not allow every member of the population not to be selected as a sample. The reliability test result is 0.76, which means it has reliability in the reliable category. The results showed: (1) readiness for the work of S-1 Guidance and Counseling students class of 2017 FIP UPI were in the very ready category as many as 13 students with a percentage of 17.57%, (2) ready category as many as 51 students with a percentage of 68.91%, and (3) there were ten students in the unprepared category with a percentage of 13.51% so that there are 61 students from 74 students who are in the ready and less ready categories.Keywords: early adult; work readiness; guidance and counselingMahasiswa semester enam berada pada rentang usia 19-22 tahun sehingga dapat dinyatakan sebagai individu dewasa awal. Tugas perkembangan dewasa awal meliputi memilih pasangan/pasangan nikah dan mulai bekerja dalam suatu posisi. Kesiapan kerja mahasiswa semester enam ini masih dicemaskan dengan minimnya pengetahuan dan kompetensi yang akan menunjang karir masa depan mereka. Penelitian ini bertujuan untuk: 1) mendeskripsikan tingkat kesiapan kerja siswa; dan 2) mendeskripsikan program bimbingan dan konseling yang dapat dilaksanakan untuk meningkatkan kesiapan kerja siswa. Penelitian ini dilakukan pada mahasiswa S-1 Bimbingan dan Konseling angkatan 2017 FIP UPI. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan metode penelitian variabel kesiapan kerja. Sampel penelitian berjumlah 74 siswa dengan teknik pengambilan sampel menggunakan pendekatan nonprobability sampling dengan teknik sampling jenuh yang tidak memungkinkan setiap anggota populasi tidak dipilih sebagai sampel. Hasil uji reliabilitas sebesar 0,76 yang berarti reliabilitas dalam kategori reliabel. Hasil penelitian menunjukkan: (1) kesiapan kerja mahasiswa S-1 Bimbingan dan Konseling angkatan 2017 FIP UPI berada pada kategori sangat siap sebanyak 13 mahasiswa dengan prosentase 17,57%, (2) kategori siap sebanyak 51 siswa dengan persentase 68,91%, dan (3) terdapat 10 siswa dalam kategori tidak siap dengan persentase 13,51%. Sehingga terdapat 61 siswa dari 74 siswa yang berada pada kategori siap dan kurang siap.Kata kunci: dewasa awal; kesiapan kerja; bimbingan dan konseling